Optimization of indications for computed tomography in children and adolescents with respiratory tuberculosis - I. Yu. Petrakova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
The purpose of the work is to optimize radiation exposure in children and adolescents with respiratory tuberculosis.Object and methods. The retrospective study included 401 patients aged 2–17 years with various clinical forms of respiratory tuberculosis. Clinical, laboratory and X-ray comparisons were carried out during the main course of chemotherapy and after its completion. The influence of CT data on patient management tactics at the stages of conservative and surgical treatment, as well as its role in the subsequent follow-up of patients, was analyzed.Results. Indications and timing of CT scans of the chest organs in children and adolescents with respiratory tuberculosis were determined.